The Impact Of Determinants Of The Financial Sector On Financial Inclusion In Syria And The Neighboring Countries (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The financial system plays an important role in the economies of countries, Because of its overlap and interdependence with many variables of economic activity. Thus, an efficient financial system enhances economic and financial stability, and promotes investment and growth. For an advanced financial system, This financial system must be based on a broad popular base, this means "financial inclusion", So the access of financial services to the largest segment of citizens (financial inclusion) is directly related to the progress and development of the financial system and thus economic and social development at the micro and macro levels.This paper aimed to study some of the determinants related to the structure of the financial sector on financial inclusion "availability of banking services ", in Syria and neighboring countries, during the period (2004-2017).For analyzing research data, the research used the Principal Component Analysis (PCA) method to integrate the two variables of "banking services availability", that is demographic and geographical penetration, that is the number of bank branches and ATMs per (100,000 adult individuals), and per (1000) Km2. Then the stability of the search variables was tested, and one of the Panel Data models was used, which is the Random Effects Model, and the data was analyzed based on the (EViews 10).The results of the research showed, that Financial Inclusion "the index of banking services availability" in Syria is below the required level, especially when compared to the neighboring countries of Syria.The results showed that variables of Bank Concentration, Operational Inefficiency of Banks, have a significant and negative impact on Financial Inclusion. While the variables of Government Size, Political Stability has no significant impact on financial inclusion in the research sample.